(untitled) - Fant, Karl M. (Hoboken, N.J., 2005)
Logically determined electronic system design is a viable solution to manage the growing complexity of digital design in today's industry. The author shows how this new clockless design methodology is essential for securing the future economic growth of the digital design industry by removing a costly design factor and opening the door to more reliable and less expensive products.
Keywords: Asynchronous circuits,Logic, symbolic and mathematical,Logic design,Computer architecture; Design and construction